925 Maintenance of Elective Surgical Care During Covid-19 Pandemic. (12th October 2021) - Digne-Malcolm, H; Kanwal, A; Puventhiranathan, P; Phelan, L; Hamid, M; Hendrickse, C; Dilworth, M P
Abstract: Introduction: Recent publications demonstrate significant morbidity in surgical patients with concurrent COVID-19 infection. This, combined with the redistribution of resources to support the pandemic, led to abrupt cessation in planned operating. COVID-19-free 'cold' sites were established to enable elective surgery to resume with reduced risk. We evaluate the outcomes and limitations of a newly established cold site. Method: Data were collected retrospectively for all patients operated between June and September 2020 by either General Surgery or Urology. Primary outcomes were 30-day COVID-19 infection and 30-day mortality. Secondary outcomes included length of stay, 30-day complications, and need for transfer to 'hot' hospital sites. Results: 881 patients were included. No patients had a positive COVID-19 test within 30 days of their operation. 30-day mortality was 0.01% (n = 1). The mean (+/-SD) length of stay was 1.69+/-3.42 days. 12.15% (n = 107) of patients experienced a complication within 30 days and 11.7% (n = 103) were readmitted within 30 day of discharge. 3.3% (n = 29) of patients required transfer to a 'hot' hospital site. 44.8% of these were admitted to level 2 or level 3 care, 17.2% required total parenteral nutrition, and 20.7% returned to theatre. Conclusions: 'Cold' surgical sites are effective in preventing peri-operative COVID-19 infection. Elective surgery can therefore continue safely through the pandemic with such precautions. Further development of on-site resources, including provision for total parenteral nutrition and access to higher level care, will help to minimise the need for patient transfers to COVID-19 exposed sites.